About the Possible Mechanisms of the Influence of Optical Intraocular Implants on the Characteristics of Neurosensory Rehabilitation and Adaptation in Patients with Pseudophakia. Literature Review - L. Sh. Ramazanova; O. A. Napylova; R. Z. Shamratov (Oftalʹmologiâ, 2021)
This literature review analyzed the possible mechanisms of the influence of the design features and optical characteristics of monofocal intraocular lenses (IOLs) on the characteristics of sensorineural adaptation and visual rehabilitation in patients after cataract phacoemulsification. Bibliographic research of scientific publications was carried out in the following databases: Medline, Pubmed, Cochrane, eLibrary. Languages of publications: Russian and English. The literature review reflects research data on the physicochemical properties, optical surface and color of the IOL filter, spatial contrast sensitivity and wavefront aberrations. Analysis of domestic and foreign literature has demonstrated the absence of a systematic approach to the study of sensorineural adaptation in patients after implantation of monofocal IOLs, which would make it possible to reasonably develop requirements for qualitative and constructive characteristics in the production of intraocular lenses to improve the quantitative and qualitative indicators of their visual functions in order to reduce the terms of rehabilitation and improvement of quality of life indicators in patients with pseudophakia. At the same time, there is an obvious need for research on the influence of the design and quality characteristics of optical intraocular implants on the subjective “quality of vision” of patients with pseudophakia, which is, ultimately, the target indicator of cataract surgery at the present stage. Also, the key mechanisms of neurosensory rehabilitation and adaptation of patients who underwent cataract surgery need to be studied and clarified in order to develop recommendations for the production of intraocular implants.